Blackwater - Arroyo, Jeannette (Henry Holt Books and Company, 2022)
"Set in the haunted town of Blackwater, Maine, two boys fall for each other as they dig for clues to a paranormal mystery. Tony Price is a popular high school track star and occasional delinquent aching for his dad's attention and approval. Eli Hirsch is a quiet boy with a chronic autoimmune disorder that has ravaged his health and social life. What happens when these two become unlikely friends (and a whole lot more...) in the spooky town of Blackwater, Maine? Werewolf curses, unsavory interactions with the quarterback of the football team, a ghostly fisherman haunting the harbor, and tons of high school drama"--Provided by publisher.